PEMODELAN PENYEBARAN INFEKSI COVID-19 DI KALIMANTAN, 2020 - Teguh, Rony; Sahay, Abertun Sagit; Adji, Fengky F (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
In the regional scale of the province in Kalimantan, the spread case appeared in West Kalimantan and East Kalimantan on 18th March 2020, Central Kalimantan on 20th March 2020, South Kalimantan on 22nd March 2020 and North Kalimantan on 29th March 2020. In this case the Covid-19 epidemic was caused by coronavirus disease 2019 (Covid-19). The prediction of the Covid-19 is currently sought. We use the SIR Model to perform basic reproductive value calculations (R0). This model is the mathematic language, interpreted as the number of nativity of a new case due to a person infected with Covid-19 into a fully healthy and potential population for illness or infection by the Covid-19. Using the linear regression, we estimate the value of R0. The value of R0 in Kalimantan region is West Kalimantan (R0 = 1.15), East Kalimantan (R0 = 1.17), Central Kalimantan (R0 = 1.09), South Kalimantan (R0 = 1.24), and North Kalimantan (R0 = 1.20). According to the SIR Model, the highest R0 value is in South Kalimantan, followed by North Kalimantan, East Kalimantan, West Kalimantan, and Central Kalimantan.